ANATOMICAL PROPERTIES AND FIBER QUALITY OF FIVE POTENTIAL COMMERCIAL WOOD SPECIES FROM CIANJUR, WEST JAVA - Ratih Damayanti; Sri Rulliaty (Indonesian Journal of Forestry Research, 2010)
A detailed description of wood anatomy is essential for assessing the use of a wood species for processing , and also beneficial for the identification of wood samples. Computerized keys are available that allow the identification of wood samples until the genus level; however, it is not easy to use these keys to identif y unknown species. Therefore, a database of anatomical characteristics and the computerized keys need to be completed up to species level. As the relevance, this study has examined the wood anatomical properties of the five corresponding tree species originated from Cianjur, West Java, which are commercially potential for their exploitation, i.e Castanopsis acuminatissima ADC. (Fagaceae); Castanopsistungurrut ADC. (Fagaceae); Cinnamomum inners Reinw. ex Blume (Lauraceae); Ficus nervosa Heyne (Moraceae) and Horsfieldia glabra Warb. (Myristicaceae). Expectedly the results would be beneficial for wood identification purposes and evaluation for other possible uses. Obser vations on anatomical structures covered macroscopic and microscopic characteristics were carried out through the sectioned and macerated wood samples. The obser ved characteristics of the anatomical features were defined conforming to the IAWA List of Microscopic Features for Hardwood  Identification.  Based on the scrutiny on those obser ved characteristics and linked to the fiber quality, it was judged that the fiber in all the five wood species could be classified as class I for pulp and paper processing.